Elevation gradient shapes microbial carbon and phosphorous limitations in the Helan Mountains, Northwest China - Wu, Mengyao; Liu, Zhen; Chen, Lin; Pang, Danbo; Xu, Xuelei; Zhang, Yaqi; Ni, Xilu; Hu, Yang; Li, Xuebin (Frontiers in Environmental Science, 2022)
Soil extracellular ecoenzymatic activities (EEA) are major players in the biogeochemical cycles and are closely related to the metabolic demand and nutrient supply in microbes. However, their effects on biogeochemistry along the elevation gradient on mountain ecosystems in arid regions remain unclear. To address this, the variations of soil microbial resource limitation and the relative contributing factors along the elevation gradient of the Helan Mountains, northwest China were investigated. The results showed that the relative abundance of total microbial, bacterial, fungal, actinomycetes, and N-acquiring enzymatic activities (N-Acetyl-β-D-glucosaminidase and Leucine- α-aminopeptidase, that is NAG and LAP, respectively) in the soil first increased and then decreased with an increase in elevation. This variation pattern could be due to the changes in soil temperature and moisture along the elevation gradient. Soil enzyme stoichiometry and resource allocation further revealed that the microbial metabolism activity in the Helan Mountains was limited by carbon (C) and phosphorus (P). Furthermore, the two limited elements were significantly higher at the mid and high altitudes (2139–2438 m) than at low altitudes (1380–1650 m). Additionally, redundancy analysis revealed that the soil water content and bulk density played crucial role in microbial community structures, while the soil pH had the most influence on soil EEA and ecoenzymatic stoichiometry. Our findings revealed the patterns of soil microbial community structure, extracellular enzyme activities, and microbial metabolism at various elevations, which will help in understanding the soil microbial limitation in mountain ecosystems.